Evaluation of pain level and patient’s satisfaction following harvesting gingival grafts from hard palate and tuberosity - حمود عرين; تهامة يوسف (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: the lateral part of hard palate is considered the most common site for harvesting free gingival grafts (FGG), and it was used for this purpose since its first introduction in 1963. Harvesting FGG from hard palate was associated with some complications, one of them was pain level in the donor site in post-operative period. So it was suggested using maxillary tuberosity as an alternative donor site. Aim: To compare patient’s pain level after harvesting free gingival grafts (FGG) from two different donor sites, by using subjective (patient’s pain level) and objective (analgesic pills number) indices. And comparing patient’s satisfaction of the whole treatment after six months. Materials and methods: sixteen healthy patients aged 20-50 with single recession each were recruited for the study. In group one (G1) FGGs were harvested from hard palate (HP), while in group two (G2) FGGs were harvested from maxillary tuberosity (MT). Patients were asked to return after two weeks, and Pain level was reported by the patient using a subjective index on a scale of 0 to 10. The patients were also asked to record number of analgesic pills (ibuprofen 600mg) taken. In the six month following the procedures, patients reported self-satisfaction of the whole treatment. Results: Pain level in the HP donor site was significantly higher than in the MT donor site during the first two postoperative weeks (6,5 ± 1,3 versus 3,0 ± 1,0 respectively). There were significant differences in analgesic consumption between the two groups with higher consumption in HP group (7,25 ± 2.1) versus (4,1 ± 1,6) in MT group. There were no significant differences in terms of patient’s satisfaction. Conclusion: Within the limitations of this study, FGGs harvested from MT donor site might provide a better option than FGGs harvested from HP in terms of less postoperative pain. And this postoperative pain affects very weakly patient’s satisfaction for the whole treatment.